A healthy lifestyle persuasive design model based on behavioral analysis - Kang, Ji; Che Me, Rosalam; Kamarudin, Khairul Manami (Elsevier BV, 2024)
In real life, people are often affected by personal, environmental and other conditions, and cannot maintain a healthy life well. In order to explore the reasons behind these behaviors, this paper discusses how to help people form a healthy lifestyle from the perspective of persuasive design, this paper starts with the analysis of people's health related behavior theories, and through the three steps of literature review, questionnaire and follow-up survey. Through in-depth analysis, points out that the factors affecting healthy lifestyle are composed of three parts: the factors that influence behavior, motivation for the behavior and environment support, these factors can be divided into controllable factors and uncontrollable factors, the controllable factors can be interfered with and changed through scientific persuasive process. Then, based on the three elements of Fogg Behavioral Model, the persuasive process and the persuasive strategies in the design were deeply studied, the persuasive process and the behavior change process were combined, the correlation between the two was found, and the persuasive strategies should be adopted in the four stages of motivation, preparation, action, and maintenance were proposed. Finally, build a persuasive model of a healthy lifestyle. This model points out the four stages and influencing factors of the formation of a healthy lifestyle, provides design strategies for each stage, and provides targeted guidance and suggestions for designers.